2015
DOI: 10.4081/ripppo.2015.160
|View full text |Cite
|
Sign up to set email alerts
|

Group climate, cohesion and curative climate. A study on the common factors in group process and their relation with members attachment dimensions

Abstract: This study examined the relationships among group process measured by the Group Climate Questionnaire, the Cohesion to the Therapist Scale and Cohesion to the Group Scale, and the Curative Climate Instrument to explore higher order factors that explained the group relationship, in a sample of 91 female university students attending 6 interpersonal growth groups. Furthermore, the study examined how group member’s attachment dimensions, anxiety and avoidance, were associated to his/her perception of group relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 35 publications
0
26
1
9
Order By: Relevance
“…Cronbach Alpha levels ranged from .87-.93 for cohesion, .81-.87 for catharsis, and .79-.84 for insight (8,40). However, later studies reported lower reliability figures; .79 for cohesion, .70 for catharsis, and .34 for insight (26). Factor structure of the CCI was suggested to be less clear than it was originally suggested by Fuhriman et al (8).…”
Section: Psychometric Properties Of the CCImentioning
confidence: 51%
See 1 more Smart Citation
“…Cronbach Alpha levels ranged from .87-.93 for cohesion, .81-.87 for catharsis, and .79-.84 for insight (8,40). However, later studies reported lower reliability figures; .79 for cohesion, .70 for catharsis, and .34 for insight (26). Factor structure of the CCI was suggested to be less clear than it was originally suggested by Fuhriman et al (8).…”
Section: Psychometric Properties Of the CCImentioning
confidence: 51%
“…Catharsis is the release of emotionally suppressed material (8,26). Freud believed catharsis rescued patients from the hysterical symptoms by allowing expression of pathological impressions and affect (27).…”
Section: Introductionmentioning
confidence: 99%
“…Milbourne & Wilkinson (2015) defi ned work stress as the spiritual fatigue caused by being slowly exposed in heavy work stress; when the person felt exhausted and emptied, such physical and mental exhaustion at work would result in the lack of work enthusiasm, strong frustration, nervousness, and even insomnia, headache, anxiety, and depression (Song et al, 2015). Gullo et al (2015) divided stressors into interpersonal relationship stressor, task relationship stressor, organizational relationship stressor, and physical & mental relationship stressor.…”
Section: Work Stressmentioning
confidence: 99%
“…Company Management now demands higher quality in terms of skills, strategic vision, role awareness and development strategies that look to of the health's manager as a precondition of healthy organizations (Campbell Quick, et al, 2000;Gullo, et al, 2015). Patterns aimed to the human factor, whose object of study is merely the subject of knowledge itself (Novara and Lavanco, 2008), are embedded to the concept of the reflexivity.…”
Section: Introductionmentioning
confidence: 99%